The effect of flooding and light competition on the planting success of degraded tropical peatland - Dony Rachmanadi; Eny Faridah; Sumardi Sumardi; Peter van der Meer; Muhammad Abdul Qirom (Jurnal GALAM, 2021)
ABSTRACT Planting was done as a rehabilitation effort at degraded tropical peatland. Understanding the characteristics of the species and environmental conditions that affect plant growth will determine the success of the planting. This study aims to determine the main environmental factors that affect plants in the field so that the right species can be determined. This study used a randomized completely blocked design which was conducted in two stages, namely field testing and verification under controlled conditions in the nursery. The research treatments consisted of inundation conditions and competition with understorey. The competition factor is interpreted by the difference in light intensity at the verification stage. The species used are meranti (Shorea pallidfolia), gerunggang (Cratoxylum glaucum), terentang(Campnosperma coreacea) dan tumih (Combretocarpus rotundatus). The results showed that the inundation conditions had an effect on the survival of meranti and gerunggang species where the survival rate was 8.3%—96.3%, but it did not affect the terentang and tumih with the survival rate reaching > 80%. The growth of meranti and gerunggang tends to decrease in line with the inundation conditions, while the growth of terentang and tumih tends to increase. Meranti growth requires understorey as protection from high light intensity. The tumih and terentang show better growth without competition with understorey. The trends in the field are consistent with observations during the verification stage. The difference in the response of plants to environmental conditions determines the presence of these species in the succession stage. Keywords:rehabilitation, flooding, drainage, sequen, succession